Vitamin E and selenium concentrations of wild donkeys and their diets in the extreme desert ecosystem of Death Valley, California, versus captive donkeys - Jerele, Sara; Bischoff, Karyn; Lundgren, Erick J.; Foley, Janet; Goodrich, Erin L. (Frontiers in Conservation Science, 2026)
IntroductionVitamin E and selenium are vital micronutrients that play key roles in metabolic functions and antioxidant defense, directly influencing equid health. There are no published reference intervals for concentrations of these micronutrients in healthy donkeys. Methods: We compared serum vitamin E and whole blood selenium concentrations in wild, recently captured donkeys with concentrations in donkeys who had been managed in captivity for at least half a year at the time the blood was drawn. In addition, we assessed hematology and serum biochemistry parameters of a subset of the donkeys. We also indirectly analyzed the diet of wild donkey herds using next-generation sequencing of fecal samples. Our last goal was to establish reference intervals for vitamin E and selenium concentrations in wild and rescued donkeys. To do so, we conducted a cross-sectional study of 113 donkeys from Saline Valley and Butte Valley in Death Valley National Park (DVNP), and captive donkeys from Davis, CA, and San Angelo, TX.ResultsWild donkeys had significantly higher vitamin E concentrations (p < 0.001, difference = 180 μg/dL, CI = 132-228 μg/dL, Tukey multiple comparisons of means test). Captive donkeys, however, had significantly higher selenium concentrations (p < 0.001, difference = 4.97 μg/dL, 95% CI = 3.51-6.43 μg/dL, Tukey multiple comparisons of means test), particularly compared to the wild ones from the Butte Valley population. Reference intervals were established for these micronutrients in wild donkeys. The vitamin E reference range for wild female donkeys was 211-754 μg/dL and for wild male donkeys was 164-780 μg/dL; the selenium reference range for wild female donkeys was 8-21 μg/dL and for wild male donkeys was 12-26 μg/dL. The fecal analysis found a mixed feeding behavior in the wild donkeys, with both grazing and browsing elements, which may explain the relatively high concentrations of these nutrients.DiscussionThis study characterizes the dynamics of vitamin E and selenium concentrations in wild donkeys from Death Valley compared to captive populations, establishing species-specific reference intervals to enhance their management.